Psychiatric Morbidity Profiles of Child and Adolescent Psychiatry Out-Patients in a Tertiary-Care Hospital - Shakya, Dhana Ratna (Journal of Nepal Paediatric Society, 2010)
Background: Psychiatric morbidity is ubiquitous, affecting children, adolescents and adults. Age factors play a great role in pattern of morbidity profile. Psychiatric morbidity profile of children and adolescents may indicate different needs and priorities. Objective: This study aims to sort out referral pattern, attitude about psychiatric referral and morbidity profile among child and adolescent psychiatric out-patients in a tertiary-care general hospital. Methodology: A total of 100 consecutive child and adolescent patients in psychiatry OPD coming into contact with investigator psychiatrist were enrolled during the study period. Diagnoses were made according to the ICD-10. Results: Fifty three of the subjects were female, majority of the cases (79) were of age between 13-18 years. Main ethnicity-caste groups seeking care were Mongol, Brahmin, Chhetri and indigenous Terai tribes. People from semi-urban and urban settings predominated in this study. Great majority (more than 80%) had reached this service in the 4th or in more than the 4th step of their help seeking. Most of the subjects were comfortable and happy about psychiatric referral. More than half had presented mainly with physical and somatic complaints. Major psychiatric diagnoses encountered were mood (affective), anxiety, seizure, dissociative conversion disorders and mental retardation. Four percent of subjects had suicidal behaviours and 17% migraine headache. Conclusion: Common psychiatric diagnoses among these child and adolescent out-patients are mood, anxiety, seizure, dissociative conversion disorders and mental retardation. Key words: Attitude to psychiatric consultation; child and adolescent; out-patient; psychiatric morbidity DOI: 10.3126/jnps.v30i2.2604 J. Nepal Paediatr. Soc. May-August, 2010 Vol 30(2) 79-84